2018
DOI: 10.1161/jaha.117.007881
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients With Atrial Fibrillation Newly Recommended for Oral Anticoagulation Under the 2014 American Heart Association/American College of Cardiology/Heart Rhythm Society Guideline

Abstract: BackgroundIn March 2014, the American Heart Association updated their guidelines for the management of oral anticoagulation (OAC) in atrial fibrillation, recommending OAC for all patients with CHA 2 DS 2‐VASc ≥2. Previously, only patients with CHADS 2 ≥2 were recommended for anticoagulation. This study compared effectiveness and safety outcomes of OAC among patients who would receive OAC using the 2014 guidelines but not the 2011 guidelines.Methods and ResultsUsing claims data from a 5% sample of 2013–2014 Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Also, the 2019 updated North American AF guidelines, suggest that use of DAPT alone may be enough for AF/ACS patients who have a CHA 2 DS 2 -VASc score of 0 to 1, with constant reassessment for anticoagulation over time [5]. An observational study showed that, for an AF patient with a CHA 2 DS 2 -VASc score of 2 to 4 or a CHADS 2 score <2, OAC administration did not result in a reduction of composite ischaemic and thrombotic events and led to more bleeding instead [92]. DAPT had a higher protective effect against stroke than aspirin alone, but lesser when compared to OAC [25].…”
Section: Antithrombotic Therapy In Patients Who Developed a New Onset Of Af-complicating Acs Or Are At A Low Risk Of Thromboembolic Eventmentioning
confidence: 99%
“…Also, the 2019 updated North American AF guidelines, suggest that use of DAPT alone may be enough for AF/ACS patients who have a CHA 2 DS 2 -VASc score of 0 to 1, with constant reassessment for anticoagulation over time [5]. An observational study showed that, for an AF patient with a CHA 2 DS 2 -VASc score of 2 to 4 or a CHADS 2 score <2, OAC administration did not result in a reduction of composite ischaemic and thrombotic events and led to more bleeding instead [92]. DAPT had a higher protective effect against stroke than aspirin alone, but lesser when compared to OAC [25].…”
Section: Antithrombotic Therapy In Patients Who Developed a New Onset Of Af-complicating Acs Or Are At A Low Risk Of Thromboembolic Eventmentioning
confidence: 99%
“…Moreover, DAPT yielded a highly significant reduction in the risk of intracranial hemorrhage, although this finding might have been amplified by the use of warfarin instead of NOAC in the TAT group [ 17 , 18 ]. In a recent claim-based large observational study, the benefit of OAC in AF patients with a CHA 2 DS 2 VASc score 2–4 and a CHADS 2 score <2 before the use of OAC did not result in a lower composite risk of stroke, systemic embolism, and death (hazard ratio, HR: 1.00), yet it was associated with a higher risk of bleeding (HR: 1.70, 95% confidence interval (CI), 1.46–1.97) [ 19 ]. Finally, a temporary suspension of oral anticoagulation has been proved reasonably safe in some clinical settings: in the BRIDGE trial, patients undergoing invasive procedures who discontinued warfarin with no bridging with dalteparin did not show any increase of thromboembolic events despite almost 10 days of likely sub-therapeutic International Normalized Ratio (INR) [ 20 ].…”
Section: Prevention Of Cardioembolic Stroke and Systemic Embolic Ementioning
confidence: 99%